Metamorphosis and Self-Discovery in Selected Modern Literary Texts - Hind HANAFI (Ziglôbitha)
ABSTRACT : In contemporary literature, themes of transformation and self-realization often serve as lenses through which authors examine identity, power, and resilience. This paper investigates the interplay of metamorphosis and self-discovery in three notable works: The Witch Doesn’t Burn in This One by Amanda Lovelace, Circe by Madeline Miller, and Boy, Snow, Bird by Helen Oyeyemi. Through an in-depth comparative analysis, the paper explores how metamorphosis—both physical and psychological—operates as a conduit for empowerment and self-actualization within these texts. In Lovelace’s poetry, metamorphosis emerges as an act of personal reclamation and defiance, while Miller’s Circe depicts exile and magic as catalysts for self-determination and autonomy. In Oyeyemi’s novel, the transformations experienced by characters highlight racial and familial complexities that lead to a subtle exploration of identity and belonging. By juxtaposing these narratives, the paper investigates the intricate intersections of identity, power, and personal evolution, emphasizing how such transformations not only mirror but actively subvert societal norms. The analysis underscores the symbolic significance of elements like fire, magic, and skin across the texts, framing metamorphosis as both an individual journey and a metaphor for resistance against hegemonic structures. Furthermore, this paper situates these narratives within broader literary discourse, particularly in their engagement with contemporary concerns surrounding gender, race, and social justice. Keywords: Metamorphosis, Self-discovery, Empowerment, Identity, mythology, Social Justice.